Responsibilities and Legal Protection of Notaries as Public Officials in Issuing Covernotes Reviewed from the Perspective of Guarantee Law - Maulida Hanum, Nindy; Witasari, Aryani (TABELLIUS: Journal of Law, 2025)
Covernote is a unilateral statement from a Notary that has no binding force, as an ordinary statement, a covernote is not classified as a notarial deed. Covernotes made by Notaries in practice give rise to several legal issues. In connection with this,The author conducted the research with the aim of finding out and analyzing it legally. conducting legal research regarding the responsibilities and protection of Notaries as public officials in issuing covernotes. To find out the above objectives, the method used is a juridical-empirical method that combines legal analysis and field data. A sociological juridical approach is applied to understand the relationship between law and social conditions, as well as the challenges faced by Notaries. Primary data is obtained from interviews with Notaries, while secondary data is taken from legal sources and related literature. Qualitative analysis is used to describe the phenomenon and understand the responsibilities of Notariesand protection of Notaries as public officials in issuing covernotes. Covernotes are not classified as authentic deeds and if the issuance of a covernote causes a loss, the Notary can be held legally responsible, both criminally and civilly. Legal protection for Notaries includes preventive aspects, such as the obligations regulated in Article 16 paragraph (1) of the Notary Law, as well as repressive aspects in the form of sanctions if a violation occurs. To clarify the Notary's responsibility in issuing a covernote, special regulations are needed in the Notary Law. In addition, Notaries are advised to be careful in issuing a covernote by ensuring that the information is in accordance with the facts.